Micrometer-scale poly(ethylene glycol) with enhanced mechanical performance - Letian Zheng; Heyi Liang; Jin Tang; Qiang Zheng; Fang Chen; Lian Wang; Qi Li (Nature Communications)
Abstract Strong and lightweight materials are highly desired. Here we report the emergence of a compressive strength exceeding 2 GPa in a directly printed poly(ethylene glycol) micropillar. This strong and highly crosslinked micropillar is not brittle, instead, it behaves like rubber under compression. Experimental results show that the micropillar sustains a strain approaching 70%, absorbs energy up to 310 MJ/m3, and displays an almost 100% recovery after cyclic loading. Simple micro-lattices (e.g., honeycombs) of poly(ethylene glycol) also display high strength at low structural densities. By combining a series of control experiments, computational simulations and in situ characterization, we find that the key to achieving such mechanical performance lies in the fabrication of a highly homogeneous structure with suppressed defect formation. Our discovery unveils a generalizable approach for achieving a performance leap in polymeric materials and provides a complementary approach to enhance the mechanical performance of low-density latticed structures.